IMPLEMENTASI QANUN LEMBAGA KEUANGAN SYARIAH DALAM KONVERSI PERBANKAN SYARIAH DI ACEH - Rahmad Safitri; M. Anzaikhan; Riri Anzely (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2021)
The presence of the Qanun of sharia financial institutions in 2018 had significant implications for banks in the Aceh province, as a region that was granted special autonomy by the Indonesian government, the Aceh region was allowed to regulate its territory implicitly and did not conflict with existing regulations. in the central region. Aceh is given the authority to apply regional government regulations and apply Islamic values in these regulations. Because of that, various kinds of Qanuns were born today. The qanun that is created certainly has to go through consistent stages so that it can run according to expectations. Not only that, the Qanun was created as a forum for the Aceh government to show the traditional values of Aceh culture and create an efficient sharia economy in Indonesia. The conclusion shows that; The implementation of the Qanun on Islamic Financial Institutions has been attempted by various conventional banks through continuous conversion, but in its realization it still requires a long step because it conflicts with different banking mechanisms, methods and systems from the previous standard. In addition, customer confidence in the various obstacles in the conversion process poses a challenge in itself, as a result, this conversion process often makes customers move to Bank Aceh, which has long implemented the concept of Islamic banking.